2018
DOI: 10.1111/petr.13142
|View full text |Cite
|
Sign up to set email alerts
|

Principles of alemtuzumab immunoablation in hematopoietic cell transplantation for non‐malignant diseases in children: A review

Abstract: Alemtuzumab is a humanized mAb targeted to CD52. Alemtuzumab is highly immunosuppressive with the ability to deplete T and B cells (in addition to other immune cell lines). A growing understanding of the PKs, dosing, and timing of administration of alemtuzumab has allowed for the study of its use as a conditioning agent for allogeneic HCT. The highly immunosuppressive properties of the drug are particularly appealing in the setting of non-malignant HCT, where GVHD provides no clinical benefit and relapse of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 112 publications
1
6
0
Order By: Relevance
“…The cumulative incidence of achieving donor CD3 + chimerism of 50% or greater (criteria to wean immune suppression) is presented in Figure 3. T-cell recovery rose over the second half of the first year post-HCT, consistent with previous alemtuzumab data [13]. Kinetics of recovery of CD4 + T cells over time is shown in Figure 4.…”
Section: Engraftment/donor Chimerism/immune Reconstitutionsupporting
confidence: 89%
“…The cumulative incidence of achieving donor CD3 + chimerism of 50% or greater (criteria to wean immune suppression) is presented in Figure 3. T-cell recovery rose over the second half of the first year post-HCT, consistent with previous alemtuzumab data [13]. Kinetics of recovery of CD4 + T cells over time is shown in Figure 4.…”
Section: Engraftment/donor Chimerism/immune Reconstitutionsupporting
confidence: 89%
“…Studies that infused alemtuzumab distal to transplant showed higher rates of engraftment, but also higher rates of GVHD. 26 In one such study, patients with non-malignant diseases experienced graft failure, 43% developed acute GVHD, and 25% developed chronic GVHD. However, the patients who received "proximal" alemtuzumab had a higher rate of graft rejection (33%) and a lower rate of GVHD (11%).…”
Section: Higher Alemtuzumab Levels Correlated With Better Donor Cd3 Chimerismmentioning
confidence: 99%
“…It is often used together with fludarabine and melphalan or other chemotherapeutic agents as part of reduced intensity conditioning (RIC) regimens for allogeneic haematopoietic cell transplantation (HCT). 1 Our group previously reported the impact of peri-transplant alemtuzumab levels on acute graft vs. host disease (GVHD), mixed chimerism, and lymphocyte recovery. 2 We found that if alemtuzumab concentrations fell within the range of 0.2-0.4 μg/mL on Day 0, the incidences of GVHD and mixed chimerism were significantly lower.…”
mentioning
confidence: 99%